PENGARUH ELEMEN PENANDA PADA PENGENALAN IDENTITAS TAMAN JEPANG - Aji, Artbanu Wishnu (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2007)
Japanese garden is one of the finest gardens in the world. Its beauty has been recognizedin many countries outside Japan. Although it is difficult to be created in tropical climate such as inIndonesia, many Indonesian would like to have Japanese garden in their home. This Researchinvestigated the possibility to create Japanese garden with less element in tropical environmentwithout losing its identity. Two initial exploration studies were conducted in Kyoto and Indonesia.Fourteen traditional gardens were chosen to be explored in the first exploration study. Its aimwas to understand material and composition variation of each element in the original setting.The second one was carried out in Indonesia to find out the image of Japanese garden in theexpert's point of view. The findings of these studies were used to design ten series of pictures.Each picture contained one element of the garden which can be rated in semantic differentialscale fromweak to strong by 120 respondents. Lantern, gate, trees, stone and water basin wererated as strong element whilst fence, pond, waterfall, stone path and bridge were rated as weakelements. Five strong elements were grouped into one garden composition as well as the weakones. The garden composition picture was presented to 200 respondents in two separategroups. Each group consists of 100 respondents with one stimulus picture only. A t-test wasused to analyze the mean difference of two groups. The result shows a significant difference inrespondent's ability to recognize Japanese garden identity between group with strong gardenelements and with the weak ones.keyword : Japanese garden, garden elements, Identity